(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Anxiety can be defined as unpleasant subjective sense due to dread over something unlikely to happen, such as standing at the point of death. It is mostly accompanied by physical symptoms i.e. restlessness, fatigue, problems in concentration, and muscular tension. So, in nutshell, Perioperative anxiety is vague, uneasy feeling, the source of which is often nonspecific and unknown to the individual but known to cause abnormal hemodynamics as a consequence of sympathetic, parasympathetic and endocrine stimulation. Thus causes more difficultly in general management during operative and postoperative period. This case series is comprised of three case of pre-operative anxiety which was posted for planned ano-rectal surgeries. At the time of hospital admission, level of anxiety was quite normal in all the patients, but by lapsing time and operative period come nearer they were feeling moderate to high level of anxiety due to various individual triggering reasons. For its management, Bramhyadi tablet (500 mg) was given in 2 doses- A night before OT, at morning on day of OT along with counselling. Here, preoperative anxiety was assessed by The Amsterdam preoperative anxiety and information scale, Hamilton anxiety rating, vital parameters and overall interview with patient in 5 phases: 1- At time of admission, 2- A night before OT, 3- At morning on day of OT, 4-1 hour after OT, 5-24 Hour after OT. Mental calmness, reduction in associated physical symptoms and stability in vital parameter were suggested positive influence of Bramhyadi tablet and counselling